(untitled) (Comparative Professional Pedagogy, 2024)
The article is devoted to studying the peculiarities of the language policy in the United States and China at the present stage. It is established that the United States is known for its linguistic diversity and is considered as a monolingual society with rich linguistic resources in the form of immigrants’ mother tongues. It is stated that the main goal of language development is unification, which would be impossible if English were granted the status of an official language. It is proven that the multilingualism of the US language policy leads to well-developed multilingual skills, which ensure its international competitiveness and national security. It is established that Chinese society has an extraordinary linguistic diversity. In order to develop the Mandarin language in China and abroad, China had to make significant efforts to reform the language, simplify writing and unify characters through standardization. The article presents a comparative analysis of the main directions and trends of language policy, its mechanisms and main instruments in the context of globalization of the United States and China. It is established that one of the important results of the language policy of the United States and China within the globalization is the growth of multilingualism and multiculturalism. The United States and China have focused on the spread of English and Chinese through “language diffusion” and soft power policies. The meaning of the term “language policy” is revealed and different levels of its implementation are distinguished. The influence of immigrants on the current linguistic situation is revealed, and it is shown how changing immigration patterns lead to changes in the linguistic policy of the countries in the context of globalization. It is concluded that language development is a unique field in which cooperation between countries is mutually beneficial. The linguistic diversity of the United States and China can be associated with the growth of multilingualism and multiculturalism, and can be considered one of the important results of language policy in the context of globalization. Despite the similarity of the issues, the essence of language policy and its planning varies considerably in the US and China. There is a clear difference between the declared language policy at the state level and the choice of a certain language at the individual level, which is happens under the influence of pragmatic factors. Thus, the scope of language policy planning should be broadened to take into account the practice and language choices in different contexts.